2021
DOI: 10.21203/rs.3.rs-278595/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Occupational Exposure to Pesticides and Central Nervous System Tumors: Results from the CERENAT Case-control Study

Abstract: Background: The etiology of the central nervous system (CNS) tumors remains largely unknown. The role of pesticide exposure has been suggested by several epidemiological studies, but with no definitive conclusion. Objective: To analyze associations between occupational pesticide exposure and primary CNS tumors in adults in the CERENAT study. Methods: CERENAT is a multicenter case-control study conducted in France in 2004-2006. Data about occupational pesticide uses - in and outside agriculture - were collected… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 8 publications
4
6
0
Order By: Relevance
“…One study reported a decreased risk of meningioma for open field farming in France (OR = 3.58 [1.20‐10.7]) 10 . Regarding crop farming, AGRICAN found a risk similar to ours (Figure 1).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…One study reported a decreased risk of meningioma for open field farming in France (OR = 3.58 [1.20‐10.7]) 10 . Regarding crop farming, AGRICAN found a risk similar to ours (Figure 1).…”
Section: Discussionsupporting
confidence: 80%
“…However, our risk estimations had narrower 95% CIs, likely due to a larger number of exposed cases. Regarding viticulture, two studies found an increased risk 11,12 while one found a decreased risk but for harvesting (OR = 0.62 [0.46‐0.82]) 10 . Our results are closer to the two studies that found an increased risk, with a positive trend observed in viticulture (HR = 1.21 [0.98‐1.48]).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations